Proceso de ventas en el Comercial Ricardito Jr de la Parroquia San Juan, periodo 2022 - Gavilanes Litardo, Romario Jesús (2023)
The case study entitled "SALES PROCESS IN THE COMMERCIAL RICARDITO JR DE LA PARROQUIA SAN JUAN, PERIOD 2022", is a diagnosis of the sales situation in which various factors that affect the results at the end of the period are analyzed, with which the techniques and procedures applied at the time of sale, which is the main action to organize and represent events that generate income, were investigated. This work has been developed through the research line of Financial Management, administration, taxation, audit and control. The sales process is the series of steps necessary to attract, convert and retain customers and can be defined as a scenario that helps professionals to anticipate customer needs and capitalize on opportunities at each stage of the sales process, given that sales strategy is an approach that allows the sales force of an organization to position a company and its products in a meaningful and differentiated way to meet the needs of target customers. In this case study it was elaborated with the purpose of analyzing how the process, sales and marketing strategies are applied, as well as how it affects the development of the commercial RICARDITO JR. of the San Juan parish. The root cause method was used in which this procedure will help to identify the origin of the problem dealing with its root discerning hypotheses from qualitative data as it allowed to identify the problems of all its processes and strategies; in order to have a better understanding of the sales process in a general sense.